Self-regulation in Preschool Children: Factor Structure of Different Measures of Effortful Control and Executive Functions - Kälin, Sonja; Roebers, Claudia M. (Journal of cognition and development, 2021)
Temperamental effortful control (EC) and executive functions (EF) are two frameworks for studying self-regulation in children. Despite stemming from different research traditions, they show many conceptual and theoretical similarities and their corresponding tasks are often used interchangeably. However, little is known about how and whether the two constructs can be distinguished empirically. The present study aimed to contribute to the investigation of this issue. A sample of 230 preschool children aged 4-6 years were tested with two common behavioral EC tasks and an EC questionnaire. Furthermore, the assessment included common measures of the three subcomponents of EF, namely inhibition, working memory, and shifting. Data were analyzed using correlational and confirmatory factor analyses. In accordance with our hypotheses, we found significant positive correlations between most EC and EF measures, and a single factor model, in which all EC and EF tasks loaded significantly on the underlying factor, was supported by our results. Moreover, this latent construct generalized across gender and age. These findings show that the variety of common EC and EF tasks used in this study all seem to tap similar aspects of self-regulation and therefore support an integrated model of self-regulation encompassing EC and EF. Our results are further considered to be informative for future research using different EC and EF tasks.